Prooxidative Role of Hyperinsulinemia in Metabolic Sydrome Formation - Nelli Uzbekova; Dilorom Abdullaevna Musakhodjaeva (Intelektual Pustaka Media Utama, 2014)
The pattern of hyperinsulinemia was studied in patients with metabolic syndrome. The levels of basal insulinemia (BI), malondialdehyde (MDA) and catalaze (CA) as an index of oxidative stress and some metabolic parameters have been studied in men and women with metabolic syndrome. Basal insulinemia correlated significantly with malondialdehyde levels both in men and women. Close relationship was also found between basal insulinemia and waist circumference.